Prescribed fire reduces insect infestation in Karuk and Yurok acorn resource systems - Halpern, Arielle A.; Sousa, Wayne P.; Lake, Frank K.; Carlson, Thomas J.; Paddock, Will (Forest ecology and management, 2022)
•Non-traditional prescribed fire reduces larval infestation in tanoak acorns during the burn year but not one year-post fire.•Vertebrate frugivory reduced the density of edible acorns.•Seasonally-specific fire is critical to the maintenance of Karuk and Yurok resource systems. Prescribed fire is used extensively as a management tool in fire-adapted landscapes of the American West to maintain ecosystem structure and function while reducing wildfire risk. Seasonally specific prescribed fire is used by many Indigenous groups to increase the quality and quantity of cultural resources and promote desired patterns of habitat diversity. Traditionally, the Karuk and Yurok Tribes of California applied fire in tanoak (Notholithocarpus densiflorus, Fagaceae) acorn gathering areas during the fall to reduce infestation in acorns by larvae of the filbertworm (Cydia latiferreana, Tortricidae) and filbert weevil (Curculio occidentalis, Curculionidae). It has become increasingly difficult to select culturally appropriate times in which to apply fire as a resource management tool due to changing environmental conditions and associated political considerations. To assess the effect of non-traditional management on tribal acorn resource systems, we investigated the effects of early summer burning on rates of larval infestation in tanoak acorns. We also studied how competing frugivores affected the availability of edible acorns to human consumers. We found that non-traditional early summer prescribed fire significantly reduced rates of larval infestation during the burn year (36.7%) but no difference between treatments was detected one year-post fire. Selective vertebrate frugivory significantly reduced the density of edible acorns by 39%. Our results highlight the importance of seasonally-specific prescribed fire in managing Karuk and Yurok resource systems and supporting tribal eco-cultural revitalization.